Uncertainty-based overestimation in the perception of group actions. (February 2021) - Khaw, Mel W.; Nichols, Phoebe; Freedberg, David
Abstract: Individuals are adept at estimating average properties of group visual stimuli, even following brief presentations. In estimating the directional heading of walking human figures, judgments are biased in a peculiar manner: groups facing intermediate directions are perceived to be more leftward- or rightward-facing than actual averages. This effect was previously explained as a repulsive bias away from a central category boundary; groups along this boundary (directly facing the observer) are estimated with lower variability and with relatively greater accuracy. Here we show that: (i) the original effect replicates and is constant over time in a novel estimation task with persistent directional states; and, (ii) novel patterns of response variability and durations align with the entire range of overestimation. A simple model of additive errors proportional to viewer uncertainty matches the observed bias magnitudes. We furthermore show that the bias generalizes beyond approaching walkers with the use of rearward-facing walkers presented at a nonparallel angle. Overall, the recurring relation between bias and uncertainty is also consistent with top-down and post-perceptual causes of misestimation.